Study of height-spread sporadic-E layers observed in the South American Magnetic Anomaly - Moro, Juliano; Xu, Jiyao; Bageston, José Valentin; da Silva, Lígia Alves; Resende, Laysa Cristina Araújo; De Nardin, Clezio Marcos; Andrioli, Vânia Fátima; Santos, Angela Machado; Picanço, Giorgio Arlan da Silva; Li, Hui; Zhengkuan, Liu; Wang, Chi; et al. (Frontiers in Astronomy and Space Sciences, 2025)
Spread echoes from the E-region observed in ionograms obtained at high latitudes are generally classified as auroral sporadic-E (Esa) layers. These layers have also been detected in nighttime ionograms collected at some ionospheric stations in the South American Magnetic Anomaly (SAMA) region in Brazil during the recovery phases of geomagnetic storms. However, similar echoes have also been observed in the SAMA during geomagnetically quiet periods or daytime, which are not caused by energetic particle precipitation. Therefore, investigating the occurrence of these spread echoes over a longer period, rather than focusing solely on case studies, has become important. Thus, this study aims to analyze the occurrences of spread echoes from the E-region, referred to here for the first time as “Height-Spread Es (HSEs) layers.” The analysis is based on Digisonde data obtained at the Santa Maria station (29.7° S, 53.8° W, ∼22.000 nT) in Brazil over 1 year (2019/2020). The study initially presents examples of these traces on ionograms and then examines their occurrence rates over several time intervals (hours, months, seasons). Among other findings, the statistical analysis reveals that the occurrence rate of HSEs layers is 9.8% during the analyzed period. The HSEs layers appeared predominantly at night and under geomagnetically quiet conditions. Most HSEs layers lasted between 1 h and 3 h 30 min, with a peak incidence during November, December, and January. Finally, the study discusses the most likely mechanisms responsible for HSEs layer formation, considering the geomagnetic conditions and time of their detection on ionograms.